2017
DOI: 10.1002/cncr.31063
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pattern of TP53 mutations in human immunodeficiency virus–related head and neck squamous cell carcinoma

Abstract: BACKGROUND Human immunodeficiency virus–infected individuals (HIVIIs) have a higher incidence of head and neck squamous cell carcinoma (HNSCC), and clinical and histopathological differences have been observed in their tumors in comparison with those of HNSCC patients without a human immunodeficiency virus (HIV) infection. The reasons for these differences are not clear, and molecular differences between HIV‐related HNSCC and non–HIV‐related HNSCC may exist. This study compared the mutational patterns of HIV‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
(120 reference statements)
1
15
0
Order By: Relevance
“…Specifically, isoflavones are a type of naturally occurring isoflavonoids, which act as phytoestrogens in mammals, their targets were mainly distributed in module 1, 2, and 5 ( Supplementary Figure 6 ). Previous researches indicated that BRCA1 in module 1 was associated with risk of estrogen-receptor-negative breast cancer ( Milne et al, 2017 ), NFE2L2 in module 3 was related with cell multisystem disorder ( Huppke et al, 2017 ), and TP53 in module 5 was related with human immunodeficiency virus-related head and neck squamous cell carcinoma ( Gleber-Netto et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, isoflavones are a type of naturally occurring isoflavonoids, which act as phytoestrogens in mammals, their targets were mainly distributed in module 1, 2, and 5 ( Supplementary Figure 6 ). Previous researches indicated that BRCA1 in module 1 was associated with risk of estrogen-receptor-negative breast cancer ( Milne et al, 2017 ), NFE2L2 in module 3 was related with cell multisystem disorder ( Huppke et al, 2017 ), and TP53 in module 5 was related with human immunodeficiency virus-related head and neck squamous cell carcinoma ( Gleber-Netto et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent report compared the pattern of mutations among HIV-related and non-HIV related head and neck SCC in genes known to be frequently mutated in such tumours and identified a different pattern of nucleotide changes in all mutated genes including TP53 [ 22 ]. Particularly, they observed an enrichment of C>T changes in the HIV-infected cases likely caused by the cytosine deamination [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have compared the mutation profile of tumours arising in HIV-positive patients versus those without HIV infection. Gleber-Netto et al [ 22 ] analyzed the nucleotide sequence of 18 genes in HIV-related and non-HIV-related head and neck SCC and showed that among HIV-positive patients the mutations tended to be TpC>T in all mutated genes but especially in TP53. This type of nucleotide change is mainly caused by the activity of APOBEC family cytosine deaminases as host defence against viral infections which also cause nucleotide mutations in human DNA [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was shown that human papilloma virus (HPV) is involved in the pathogenesis of a subgroup of HNSCCs. HPV is a risk factor for cancer of the oropharynx, particularly in tumors that are not associated with p53 mutations or with other risk factor such as tobacco and alcohol [ 22 , 23 ]. Based on this evidence it has been suggested that oropharyngeal cancer develops through two different pathways: the first one related to tobacco/alcohol consumption and p53 mutation, and the second one to HPV infection and genome instability.…”
Section: Introductionmentioning
confidence: 99%